Comparison between intraoperative and postoperative surgical outcomes of laparoscopic partial nephrectomy and open partial nephrectomy: laparoscopic versus open partial nephrectomy - Sharma, Sachin; Swain, Samir; Panda, Sabyasachi; Tripathi, Abhilekh; Yash Manharlal, Tilala; Behera, Kishore Kumar; Anshuman, Jatin (International Journal of Research in Medical Sciences, 2023)
Background: The aim of the study was to compare intraoperative and postoperative surgical outcomes of laparoscopic partial nephrectomy (LPN) and open partial nephrectomy (OPN). Methods: We did prospective retrospective study on 33 cases of renal mass operated as partial nephrectomy (PN) (15 LPN and 18 OPN) in department of urology and renal transplant SCB medical college Cuttack Odisha from 1 may 2019 to 1 may 2023. Surgical outcome of both approaches compared based upon intraop time, estimated blood loss, ischemia time, hospital stay, complications and rise in creatinine. Results: Mean intraop time 140.66 min in OPN vs 172.8 min in LPN (p<0.05-significant), mean estimated blood loss was 453 ml in OPN vs 345 ml in LPN (p=0.113-not significant), mean ischemia time was 15.88 min in OPN vs 20.53 min in LPN (p<0.05-significant), mean post op hospital stay was 7.5 days in OPN vs 6.3 days in LPN (p=0.184-not significant). Intra-op complications was 2 (11.11%) in OPN vs 2 (13.33%) in LPN and postop complications was in 5 (27.7%) in OPN vs 4 (26.66 %) in LPN. Mean rise in creatinine was 0.25 in OPN vs 0.29 in LPN (p=0.642-not significant). Conclusions: LPN is a feasible and safe alternative to OPN with comparable surgical outcomes but operating time and ischaemia time is significantly more in LPN as compare to OPN.